Efektivitas Pendekatan Realistic Mathematics Education (RME) Terhadap Kemampuan Pemecahan Masalah pada Soal Cerita - Sundari, Sundari; Musa’ad, Faida; Phricilia, Regina; Setyo, Arie Anang; Trisnawati, Nika Fetria; Budiarti, Marlinda Indah Eka; Layn, Muh. Ruslan (Universitas Cokroaminoto Palopo, 2025)
Students have difficulty solving math story problems because they do not understand the context and do not know how to start, due to conventional learning and lack of connection with real experiences. The purpose of this study was to determine the effectiveness of the RME approach on students' problem-solving abilities in solving story problems. The study was conducted in grade IV of SD Negeri 36 Sorong City using a quantitative method with a one-group pretest-posttest design. The instruments used included test questions (pretest and posttest), learning implementation observation sheets, student activity observation sheets, RME syntax implementation sheets, and student response questionnaires. Data analysis techniques in this study were normality tests, paired sample t-tests and -gain tests, then learning outcome completeness tests. The results showed an increase in problem-solving abilities after the implementation of the RME approach. The average posttest score was higher than the pretest, and the Wilcoxon Signed Rank Test results showed a significance of 0.000 <0.05, which means there was a significant difference between the pretest and posttest results. The N-Gain value of 0.5750 is included in the moderate category. The classical learning completion rate reached 84% and was in the very good category. The implementation of learning and RME syntax each achieved an average of above 85%, which is included in the very good category. Student activity also showed high results, with the majority of students in the active and very active categories. The results of the student response questionnaire showed that all students gave a positive response to the learning. Based on these results, the RME approach has proven effective in improving students' problem-solving abilities in solving mathematical story problems on the topic of measuring units of length.